Pelatihan Pengenalan dan Penerapan Aplikasi Komputer Microsoft Excel pada SMU Swasta Dharmawangsa Medan - Ermayanti Astuti; Putri Yunita; Frinto Tambunan; Fitrah Sri Wahyuni; Rikha Ira Setiyawati (Yayasan Literasi Sains Indonesia, 2023)
Dharmawangsa Private High School Medan is one of the national standard schools that is required to always develop and improve the quality of education and professionalism of service to students. Training in the use of information and communication technology devices is urgently needed so that later students and students can use them properly. The students have not been able to fully use Microsoft Excel, especially material related to macros because it is not taught at school and the high cost of computer courses among students in the Medan area. One of them is to train the ability to use a word processing application, namely Microsoft Excel. Community service activities are emphasized in the form of training on how to apply Microsoft Excel for 20 students in Dharmawangsa Medan Private High School. It is hoped that with this training, students will be able to know more about the technique of using Microsoft Office by utilizing Microsoft Excel from the service activities carried out to provide experience and skills for students in using Microsoft Office. Thus, the implementation of community service activities at Dharmawangsa Private High School Medan Using Microsoft Excel provides significant benefits for improving the skills of students and students in utilizing information technology and computers, they are very enthusiastic to participate in further activities. They already understand and canoperate Microsoft Office.